2003
DOI: 10.1016/s0736-0266(03)00052-4
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps strength and volitional activation before and after total knee arthroplasty for osteoarthritis

Abstract: I/itroN'uc.tion:Patients with osteoarthritis (OA) of the knee have quadriceps weakness and arthrogenous muscle inhibition (AMI). While total knee arthroplasty (TKA) reliably reduces pain and improves function in patients with knee OA, quadriceps weakness persists after surgery. The purpose of this investigation was to assess contributions of AM1 to quadriceps weakness before and after TKA and to assess the effect of pain on AMI.Mdiod.7: Twenty-eight patients with unilateral, end-stage, primary knee OA were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
315
1
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(342 citation statements)
references
References 25 publications
15
315
1
11
Order By: Relevance
“…Pain plays a role in the ability to use the quadriceps femoris muscles [17,30]; weakness of the quadriceps has been implicated in the development of knee osteoarthrosis [2]. Strength affects function [20]; reduced physical capacity may be both a cause and a consequence of physical impairment and functional limitations [32].…”
Section: Discussionmentioning
confidence: 99%
“…Pain plays a role in the ability to use the quadriceps femoris muscles [17,30]; weakness of the quadriceps has been implicated in the development of knee osteoarthrosis [2]. Strength affects function [20]; reduced physical capacity may be both a cause and a consequence of physical impairment and functional limitations [32].…”
Section: Discussionmentioning
confidence: 99%
“…8 In patients, superimposed electrical stimulation is used to assess voluntary activation 9,10 or to assess changes in neural activation due to training or disuse. [11][12][13] With patients however, submaximal muscle stimulation is used frequently to calculate VA, 8,10,14,15 because submaximal currents are better tolerated. 10,16 Muscle stimulation is also easier to apply than nerve stimulation because of the location of the femoral nerve in the femoral triangle.…”
Section: Muscle Nerve 45: 841-848 2012mentioning
confidence: 99%
“…In this study, we elaborate on these observations by investigating the effects of stimulation type on actual VA, which in most studies that use superimposed stimulation is the primary parameter of interest. [10][11][12][13][14] It is assumed that there is a linear relationship between voluntary torque of the stimulated muscle and superimposed torque. This indicates that VA is also related linearly to voluntary torque.…”
Section: Muscle Nerve 45: 841-848 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Total knee arthroplasty (TKA) is an effective treatment to reduce pain and subjective disability in patients with osteoarthrosis of the knee, but several studies have shown that muscle strength deficiency [1][2][3] and functional limitations may persist for several years after the operation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%